(untitled) (Bangladesh Journal of Urology, 2025)
Background: Important prognostic factor in penile cancer is Inguinal lymph node involvement. Inguinal lymph node dissection allows staging and treatment of inguinal nodal disease. Inguinal lymph node dissection causes morbidity and is associated with complications, such as lymphocele, skin loss and infection. Video Endoscopic Inguinal Lymphadenectomy (VEIL) is an endoscopic procedure, and it seems to be a new and attractive approach duplicating the standard open procedure with less morbidity. We present here a critical perioperative assessment with points of technique. Methods: Five patients with moderate to high grade penile carcinoma with clinically negative inguinal lymph nodes were subjected to elective VEIL. All VEIL were performed at department of urology, square hospital from 2020 to 2024.VEIL was done in standard surgical steps. Perioperative parameters were assessed that is - duration of the surgery, lymph-related complications, time until drain removal, lymph node yield, surgical emphysema and histopathological positivity of lymph nodes. Results: Operative time for VEIL was 150 to 210 minutes. Lymph node yield was 7 to 12 lymph nodes. No skin related complications were seen with VEIL. Lymph related complications, that is, lymphocele, were seen in only one patient. The suction drain was removed after four to eight days (mean 5.1). Overall morbidity was 20% with VEIL. Conclusion: VEIL is a safe and feasible technique in patients with penile carcinoma with non palpable inguinal lymph nodes. It allows the removal of inguinal lymph nodes within the same limits as in conventional surgical dissection and potentially reduces surgical morbidity. Bangladesh J. Urol. 2025; 28(1): 3-9